Polish society under German occupation : the Generalgouvernement, 1939-1944 - Gross, Jan Tomasz (Princeton University Press, 1979)
By combining historical and political analysis with a sophisticated sociological approach, Jane Gross offers a new interpretations of the German occupation of Poland during World War II. Based on his hypothesis that a society cannot be destroyed by coercion short of the physical annihilation of its members, his work has a twofold aim; to examine the model of German occupation in theory and in practice, and to identify the patterns of collective behavior that emerged among the Polish people in response to the social control exercised over them. The author argues that when an occupier provides no institutions through which a local population can at least minimally satisfy its social needs, the subjugated populace builds substituted institutions on the remnants of previous forms of its collective life. These substitutes constitute the society's self-defense, to which the occupier must in some way adjust if its goals of manipulation and exploitation are to be achieved. Professor Gross points out numerous ways in which the Poles under the General government circumvented the goals and authority of the German occupiers. Most significant was the emergence of the Polish underground, which took on the leadership, social welfare, political, and financial functions of an independent state. This phenomenon, he concludes, shows that resistance should not be conceived merely as a military movement but rather as a complex social phenomenon. Jan Tomasz Gross is Assistant Professor of Sociology at Yale University. Originally published in 1979.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.